2016
DOI: 10.1111/apha.12826
|View full text |Cite
|
Sign up to set email alerts
|

PGC‐1α4 gene expression is suppressed by the IL‐6—MEKERK 1/2 MAPK signalling axis and altered by resistance exercise, obesity and muscle injury

Abstract: Our findings reveal a novel mechanism suppressing Pgc1α4 gene expression via IL-6-ERK-MAPK and suggest this signalling axis may inhibit Pgc1α4 in some, but not all, (patho)physiological conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
30
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 46 publications
2
30
0
Order By: Relevance
“…There are several PGC-1 isoforms, and each has significant but independent roles in oxidative metabolism. PGC-1 α 4 regulates muscle protein synthesis through IGF-1 and myostatin signaling cascades [133, 134]. PGC-1 β can regulate myosin heavy-chain isoform expression, and increased expression induces an oxidative muscle phenotype [135].…”
Section: Mitochondrial Dysfunction In Cachectic Muscle and Inflammmentioning
confidence: 99%
“…There are several PGC-1 isoforms, and each has significant but independent roles in oxidative metabolism. PGC-1 α 4 regulates muscle protein synthesis through IGF-1 and myostatin signaling cascades [133, 134]. PGC-1 β can regulate myosin heavy-chain isoform expression, and increased expression induces an oxidative muscle phenotype [135].…”
Section: Mitochondrial Dysfunction In Cachectic Muscle and Inflammmentioning
confidence: 99%
“…In the manuscript by Brown et al . (), it was initially discovered that global deletion of IL‐6 in mice increased PGC‐1 α 4 expression in the skeletal muscle nearly sevenfold, supporting a link between IL‐6 expression/signalling and the expression of this splice variant. Further mechanistic work in C 2 C 12 myotubes showed that exogenous IL‐6 administration effectively decreased PGC‐1 α 4 expression through a MEK/ERK sensitive mechanism.…”
mentioning
confidence: 97%
“…, Brown et al . ). Alternatively, the transient MEK/ERK activation following resistance exercise may be a different stimulus compared to the more chronic activation that appears to occur with ageing (Brown et al .…”
mentioning
confidence: 97%
See 2 more Smart Citations